Quality of life assessment with the SF-36 instrument during the COVID-19 pandemic: A pilot study (Research, Society and Development, 2021)
The objective of this study was to evaluate the quality of life of healthy volunteers through the SF-36 questionnaire by telephone contact during the COVID-19 pandemic in the city of Machado/MG. The SF-36 is a multidimensional questionnaire composed of 36 items, encompassed in eight scales or components: functional capacity, physical aspects, pain, general health status, vitality, social aspects, emotional aspects, mental health, and one more question comparing current health conditions to those of one year ago. It assesses both the negative aspects of health (illness or disease) and the positive aspects (well-being). 114 volunteers were interviewed between November 2020 and January 2021. Of these, 52 (45.6%) were female and 62 (54.4%) were male.  The mean age of the sample studied was 34.99 years (SD 12.01). Statistical analysis was done using the statistical program SPSS version 2.0. The independent t-test was used for the comparison of mean and standard deviation between genders and the domains of the SF-36 questionnaire, and Pearson's correlation coefficient classified the correlation as perfect (r=1), strong (r>0.75), moderate (r>0.5), weak (r